Nonalcoholic fatty liver disease: Biomarkers support decisions around pharmacological intervention - Sookoian, Silvia Cristina (2017)
We read with great interest the article of Ajmera et al. (1) reporting on the relationship between bio- markers and the histological disease spectrum of nonal- coholic fatty liver disease (NAFLD) in a large population of well-characterized patients from the Non- alcoholic Steatohepatitis Clinical Research Network. The researchers found a significant association between circulating levels of total plasminogen activator inhibitor 1 (tPAI1) and the presence of nonalcoholic steatohepa- titis, which was independent of clinical confounding factors. (1) The clinical value of this result should be highlighted, also having important implications for tai- loring pharmacological interventions.